Sintilimab and Chidamide for Refractory Transformed Diffuse Large B Cell Lymphoma: A Case Report and A Literature Review - Chen, Chao; Zhang, Wei; Zhou, Daobin; Zhang, Yan (Frontiers in Oncology, 2021)
Patients with relapsed/refractory (R/R) transformed diffused large B cell lymphoma (tDLBCL) have a poor prognosis and a low survival rate. In addition, no standard therapy has yet been established for R/R tDLBCL. Herein we presented a single case of a patient with R/R tDLBCL who was successfully treated with sintilimab and chidamide. The patient was a 71-year-old man with pulmonary mucosa-associated lymphoid tissue lymphoma. He did not receive any treatment until tDLBCL was confirmed 2 years later. The tDLBCL was primary refractory to R2-CHOP, R2-MTX, and Gemox regimens. However, the patient achieved sustained complete remission after the combination therapy of sintilimab and chidamide. To the best of our knowledge, this is the first report of sintilimab combined with chidamide for the treatment of R/R tDLBCL, which opens up new therapeutic possibilities for this new combination therapy in future prospective clinical trials.